The Implementation of Phonic Method in Teaching Vocabulary in Speaking to Visually Impaired Students in SLB A (Visual Impairment) - Donni Prakosha; Abdul Salim; Sunardi Sunardi (Department of Special Education, 2018)
This research aimed to explore the implementation of phonic method in teaching vocabulary to vision impairment students. This study was a qualitative research with case study as the research design. Data in this study was analyzed by using Miles and Huberman model of analysis. It consists of data reduction, data display, and conclusion drawing. Result of this study showed that teaching documents used in the teaching-learning process of English to visually impaired students of SLB A Surakarta are curriculum, syllabus, and lesson plan. To teach effectively, the teacher uses some components to support the teaching process. The supporting components used in this teaching-learning activity related to phonic method are laptop, slate and stylus, and JAWS and TALK Program